Analysing authorial identity construction in the review article genre in Applied Linguistics - Ali Sorayyaei Azar; Azirah Hashim (Universitas Syiah Kuala, 2022)
Authorial identity construction is one of many professional rhetorical strategies employed by authors in academic review genres. Authors usually create a persona to represent themselves, their seniority in the field, and the community to which they belong. The author's visibility is made possible through several rhetorical devices. Perhaps the most remarkable way of such authorial identity construction in the review article genre is self-mentions. The aims of this research are (1) to find out what types of self-mention are frequently used in review articles, (2) to determine the frequency of use and distribution of self-mentions in the review articles, and (3) to investigate the rhetorical function of self-mentions in the different analytical sections of the review articles. The data, drawn from a randomly selected corpus of thirty-two review articles, were analysed using WordSmith Tools Version 6. The findings indicated that first-person plural pronouns were more frequently used than singular pronouns in the whole corpus except in the two review texts. It was also observed that the frequency of occurrence for the exclusive and inclusive pronouns was very close to each other. Most importantly, the inclusive pronouns were used not only as a politeness strategy to appreciate the readers and keep the writers' claims balanced but also as a persuasive tool to seek the readers' agreement in the evaluation of research developments. This study revealed that authors construct various professional personas as a rhetorical strategy to carve their authorial identity and credibility in the review article genre. The findings of this study have pedagogical implications in the field of academic writing in applied linguistics as well as other disciplines.